Peach Scab - Daniel Mancero-Castillo; Mercy Olmstead; Phillip Harmon (EDIS)
Peach scab is a disease caused by the fungus Cladosporium carpophilum. The pathogen can infect other fruits and nuts within the Prunus species, like almonds, apricots, nectarines, and plums. Peach scab is common during periods of humid weather because rain splashes the conidia (asexual spores) from the fungus between leaves, twigs, and fruit in the tree canopy, which spreads the disease. This 6-page fact sheet was written by Daniel Mancero-Castillo, Mercy Olmstead, and Phillip Harmon, and published by the UF Department of Horticultural Sciences, July 2014.